PELATIHAN PEMANFAATAN KECANGGIHAN TEKNOLOGI DALAM PENGEMBANGAN UMKM JIHU BU YUL DI DESA SOGAAN KEC. PAKUNIRAN - Khalifatus Silfia; Hamidatun Nafisah (Kalam Nusantara Institute, 2023)
Buying and selling online is increasingly popular among teenagers today. Online shopping makes it easy for us to buy an item without having to queue and jostle in shops, markets or supermarkets. And this online shopping activity takes advantage of technological sophistication, which is developing very rapidly. The objectives of this community service activity are: 1. Changing the packaging of Jihu Bu Yul so that it can be different from other Jihu. 2. The packaging includes Bu Yul's social media so consumers can more easily recognize Bu Yul's Jihu. 3. We are helping Bu Yul promote Jihunya through social media so that Bu Yul's Jihu can be better known to the wider community, especially teenagers. This community service activity was carried out in August 2021. This community service activity took place in Sogaan Village, Pakuniran District, Probolinggo Regency. The material presented in this community service activity is the material on Utilization of Technology in UMKM Development, namely by changing packaging and helping marketing through social media. At the end of the service, it was found that 1. Bu Yul's knowledge of the use of technology had increased. 2. Bu Yul's response to this activity was very positive.